2008
DOI: 10.1590/s0004-282x2008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Handedness of children determines preferential facial and eye movements related to hemispheric specialization

Abstract: -Background: Despite repeated demonstrations of asymmetries in several brain functions, the biological bases of such asymmetries have remained obscure. Objective: To investigate development of lateralized facial and eye movements evoked by hemispheric stimulation in right-handed and left-handed children. Method: Fifty children were tested according to handedness by means of four tests: I. Mono-syllabic non-sense words, II. Tri-syllabic sense words, III. Visual field occlusion by black wall, and presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…As for hand preference associated with gender, there was no significant difference, which corroborates the studies of Arteaga and Poblano (2008), Beratis et al (2009) and Preti et al (2014). Other authors (Johnston et al, 2007;Milenkovi et al, 2013) found a prevalence of left-handed men.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As for hand preference associated with gender, there was no significant difference, which corroborates the studies of Arteaga and Poblano (2008), Beratis et al (2009) and Preti et al (2014). Other authors (Johnston et al, 2007;Milenkovi et al, 2013) found a prevalence of left-handed men.…”
Section: Discussionsupporting
confidence: 85%
“…Left-handers presented a poorer performance than right-handers in the total semantic score (sum of animal, food and beverage categories) (p = 0.002). As well as the findings of Arteaga and Poblano (2008), in which left-handers took longer to recognize monosyllabic pseudowords and discriminated fewer trisyllabic words, the hypothesis is that incomplete hemispheric specialization may interfere with skills involving language in left-handers. Siengthai, KritzSilverstein, and Barrett-Connor (2008), in crosssectional study with the elderly, found that lefthanded women have lower verbal fluency than right-handers.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations